The Effect of Burpee Training on Improving 50-Meter Breaststroke Speed in Youth Club Athletes at Noren Tirta Buana - Seby Anjelica Adha; Viktor Pandra; Muhammad Suhdy (CV. Edujavare Publishing, 2026)
Swimming is an aquatic sport that demands technical skill, physical condition, and coordination to achieve optimal performance. This study aims to determine the effect of burpees training on increasing the 50-meter breaststroke swimming speed of youth athletes at Club Noren Tirta Buana. The study used an experimental method with a two-group pretest-posttest design. The study sample consisted of 20 youth athletes selected using purposive sampling techniques and divided into an experimental group and a control group of 10 people each. The experimental group was given burpees training for four weeks with a frequency of three times a week, while the control group underwent regular swimming training without burpees training. The research instrument used a 50-meter breaststroke swimming test measured using a digital stopwatch. Data analysis was carried out through normality tests, homogeneity tests, and t-tests at a significance level of 5%. The results showed that the experimental group experienced a better increase in swimming speed compared to the control group. The average value of the swimming time after treatment decreased, indicating an increase in swimming performance. The results of the hypothesis test showed a significant effect of burpees training on increasing the 50-meter breaststroke swimming speed of youth athletes at Club Noren Tirta Buana. Based on the research results, it can be concluded that burpees training is effective as a physical training method to increase the speed of 50-meter breaststroke swimming because it can increase leg muscle strength, explosive power, motor coordination, and muscle endurance which supports athlete performance when swimming.